Element transport in the Taz River, western Siberia - Pokrovsky, Oleg S.; Manasypov, Rinat M.; Chupakov, Artem V.; Kopysov, Sergey G. (Chemical Geology, 2022)
The riverine export fluxes of dissolved carbon, nutrient and metals from the land to the Arctic Ocean are fairly well quantified for five large Arctic rivers but remain virtually unknown for mid-sized Eurasian rivers, notably those draining through the permafrost zone. Because such rivers can most rapidly respond to on-going climate warming and permafrost thaw in the Arctic, their current hydrochemical composition and elemental yields are badly needed for judging the level of changes in the very near future. Towards quantifying the annual export fluxes and assessing the mechanisms of seasonal variability of river solutes, we monitored the pristine subarctic Taz River (Swatershed = 150,000 km2), which drains through boreal forest and peatlands in the discontinuous and continuous permafrost zone, on a weekly to monthly basis over a 3 year period. Based on seasonal pattern of riverine solutes (< 0.45 μm) and their dependence on discharge, 3 groups of elements were distinguished. These groups of solutes were consistent with several main sources of elements in the main stem of the Taz River such as deep groundwater, riparian zone and floodplain lake sediments, plant litter, mineral soil water, and peatwater from the peatlands. The 1st group was represented by dissolved inorganic carbon (DIC), specific conductivity, and some nutrients (NO3, NH4, Ntot and Si) and soluble elements that originated from groundwater and deep soil mineral horizons (Cl, SO4, Li, B, Na, Mg, Ca, Si, K, Rb, Mn, Co, Sr, Mo, Cs, Ba and W) and showed maximal concentration at the end of winter, before the spring ice-off. This group showed negative correlation to discharge. The 2nd group included dissolved organic carbon (DOC), low-mobile hydrolysates and organically-complexed trace metals (Al, Be, V, Ni, Y, Se, Zr, Nb, REEs, Hf, Pb and Th) which demonstrated maximal concentrations during the spring flood and autumn high flow and minimal values during winter. The concentration of these elements generally increased with water discharge, presumably ...